Mutatus gen. nov., a new genus of Phrurolithidae (Arachnida, Araneae) from China, with descriptions of four new species - Yannan Mu; Luyu Wang; Feng Zhang; Zhisheng Zhang (ZooKeys)
Mutatus gen. nov. is described from southwest China, including four new species: M. gelao sp. nov. (♂♀, Guizhou Province), M. tianyan sp. nov. (♂♀, Hubei Province), M. tujia sp. nov. (♂♀, Hubei Province), and M. yintiaoling sp. nov. (♂, Chongqing Municipality). This new genus can be differentiated from other phrurolithid genera by the male palp which has a prolateral tegular apophysis and tegular sheet, and by a small protuberance on the female epigynal plate.